PERSONAL, HOME AND SOCIAL FACTORS AS DETERMINANTS OF FEMALE STUDENTS’ ENROLMENT AND COMPLETION IN UNIVERSITY EDUCATION IN SOUTHWESTERN NIGERIA, 2001-2010 (2016)
Female students‘ enrolment and completion in university education in Nigeria was low between 2001-2010. These have been attributed to some personal, home and social factors which have inhibited many females from being enrolled and completing university education in some courses. Previous studies examined the link between these factors and low female enrolment and completion at the primary and secondary school levels without focusing on Science Education, Engineering, Agriculture, Law, Mathematics and Statistics at university level. This study, therefore, examined personal (age, role model with mentorship and feminine inclination), home (mothers‘ education, fathers‘ education, parent‘s socio-economic status and parental support) and social (school environment, socio cultural value, government and non-governmental involvement) factors as determinants of female students‘ enrolment and completion in these universities courses from 2001-2010.The study adopted a causal modelling design with two hypothesised models. Six government-owned universities (one per state) from the south-west were selected. They comprised three states (Adekunle Ajasin, Ekiti State and Olabisi Onabanjo Universities) and three federal (University of Ibadan, Obafemi Awolowo University and University of Lagos). Stratified and purposive sampling techniques were used to select 622 female final and penultimate year students from five courses (Mechanical engineering (37), Civil law (207), Mathematics and Statistics (38), Science Education (164) and Agriculture (176). Role model and mentorship (r=0.75), feminine inclination (r=0.89), parents socio-economic status (r=0.87), parental involvement (r=0.83), school environment (r=0.79), traditional and cultural value (r=0.76) and government and non-governmental involvement (r=0.83) inventories were used to collect data. Key informant interview was also used. Data were subjected to multiple regression, path analysis at 0.05 level of significance and content analysis.The 10 factors had significant joint contributions to female enrolment and completion in university education (F(9,612) =26.46; R2=0.28) and (F(9,612)=15.44; R2=0.20), accounting for 28.0% and 20.2% of their variances respectively. Role model with mentorship (β=.29), school environment (β=.29), had relative contributions to enrolment while parental support (β=.23) age (β=19) and socio-cultural value (β=19) had relative contributions to completion. There was no significant difference between the hypothesised and the reproduced models. The percentage of direct and indirect effects were 55.6% and 44.3% on enrolment while on completion were 67.3% and 38.7% respectively. There were 62 pathways, where eight and 54 exert direct and indirect causative effects on enrolment, and 103 pathways where seven and 96 exert direct and indirect effects on completion. Content analysis revealed that there was attrition despite low enrolment of female students across the courses examined.Role model with mentorship and school environment factors had casual effects on enrolment pattern while parental support, age and socio-cultural values were key determinants of completion of university education among female students in Nigeria. These factors should be taken cognizance of in order to improve female enrolment and completion of courses at the university level